Analyzing the Secondary Metabolites and Pharmacological Activities of Solanum ferox: A Systematic Review - Depasthika, Sistha Citra; Riyanto, Izory Roman; Masriani; Muharini, Rini (Universitas Pendidikan Mandalika, 2025)
This study explores Solanum ferox, also known as Solanum lasiocarpum Dunal, as a rich source of secondary metabolites in herbal medicine. The main objective of this article is to highlight the secondary metabolites contained in S. ferox. The methodology employed is a Systematic Literature Review, following the PRISMA guidelines, which analyzes 8 selected articles published from 2018 onwards. These articles were sourced from Google Scholar, PubMed, and Mendeley databases, focusing on studies related to the phytochemistry of this plant. the results of the document analysis show Solanum ferox contains various compounds such as alkaloids, flavonoids, tannins, terpenoids, steroids, and saponins, which demonstrate significant potential in antioxidant, antibacterial, and anticancer activities. These results also indicate the possible structures of the identified compounds, providing a deeper understanding of their bioactivity. Moreover, this study highlights how the diverse phytochemical profile of Solanum ferox supports its traditional use in herbal remedies. These findings emphasize the importance of further research to optimize the utilization of Solanum ferox in the development of safe, effective, and sustainable herbal medicines.